Digital trade harnessing artificial intelligence - EUM, Min Yong (KDI School, 2024)
In the first two decades of this century, we witnessed the most innovative and influential development of data-driven AI technologies including digital trade harnessing artificial intelligence. However, only a few studies have focused on the intersection between digital trade, AI, and big data- a term often quasi-synonymously used with AI. Nonetheless, this is an important emerging field and disruptive technology. The study adopts a mixed analysis to answer the research questions. The study analyzes emerging fields such as digital trade and artificial intelligence and its intersections. Although there are problems of relating to lack of recent empirical studies on intersections between digital trade and AI, the study does suggest trust regulatory environment for international collaboration using trustworthy AI in the digital trade given conditions 1) ongoing fierce competition between the US and China, and also 2) relatively weak moderating role by the EU. Asia-Pacific initiative by Singapore, Australia, Japan and South Korea might be a potential alternative to devise regulatory frameworks for AI, although getting a consensus and reaching an international agreement are becoming difficult among the major players.
Thesis(Master) -- KDI School: Master of Development Policy, 2024
Keywords: Electronic commerce; Artificial intelligence--Economic aspects